Wrapping XEROS RESIDENCE in a veil of rusted steel, Blank Studio borrows hues from the desert landscape. - Stephens, Suzanne (Architectural Record, 2006)
The article describes the architectural design of the Xeros Residence in Phoenix, Arizona designed by Blank Studio. The residence looks like a treehouse or a huge periscope from various angles. On its upper level, architect Matthew Trzebiatowski oriented the living/dining/kitchen area to the south and the bedroom to the north. The base of the house contains a library and studio and is partially enclosed by concrete walls. Steel was used for the handrails, the entry stairs and the structural frame.